Where next for youth mental health services in Ireland?. (1st June 2018) - McMahon, J.; Ryan, F.; Cannon, M.; O'Brien, G.; O'Callaghan, M.; Flanagan, R.; O'Connor, K.; Chambers, D.; Byrne, S.; McGorry, P.
Abstract : To date, Ireland has been a leading light in the provision of youth mental health services. However, cognisant of the efforts of governmental and non-governmental agencies working in youth mental health, there is much to be done. Barriers into care as well as discontinuity of care across the spectrum of services remain key challenges. This editorial provides guidance for the next stage of development in youth mental care and support that will require significant national engagement and resource investment.